Implementasi Budaya Ketaqwaan Bagi Mahasiswa Di STAI Al-Hidayah Bogor - Jamaludin, Jamaludin; Na'imah, Farida Ulvi; Fatikh, M. Alfin (LP3M STIT Al Urwatul Wutsqo Jombang, 2024)
This research aims to examine implementing a culture of devotion to increase the spiritual intelligence of students at the Al-Hidayah Bogor Islamic College (STAI). This research collects data through observation, interviews, and document study using a qualitative approach. The results of the research revealed 19 forms of devotional culture that were applied, such as tahfidz tahsin Al-Qur'an, infaq, smile-greeting-greeting, politeness, dhuha prayer, dhikr, pilgrimage rituals, and tolerance. Implementing a culture of devotion is carried out using an instructive sequential strategy based on structural aspects, including school policy, the commitment of the school community, creating an atmosphere of devotion, internalization of values, example, and habituation. The commitment of school leaders, the gradual process of internalizing values, an exemplary and persuasive approach, and habituation are the keys to successful implementation. The positive impact can be seen in the behavior of students who have good morals, high tolerance, a spirit of mutual help, self-confidence, honesty, discipline, a broad understanding of religion, and deep faith and devotion. The results of this research strengthen the theory regarding the importance of implementing the values ??of devotion to form spiritual intelligence and can be a reference for other educational institutions in designing similar strategies.